Emergency management and it’s effect on clinical profile of Fournier’s gangrene in patients presenting at a rural setup - Syed, Tausif Kamal; Apturkar, Dilip K.; Dandekar, K. N. (International Surgery Journal, 2019)
Background: Fournier’s gangrene (FG) is a rare, rapidly progressive, necrotizing fasciitis of the external genitalia and perineum, leading to soft-tissue necrosis. Despite antibiotics and aggressive debridement, the mortality rate of FG remains high. This study describes our experiences in the management of FG and identifies prognostic factors. Methods: It is a descriptive prospective study in 71 patients with FG treated at Pravara Rural Medical College and Hospital, Loni, who presented between September 2013 and September 2015. Results: In the present series of 71 patients, 57% were between 50-70 yrs. UTI and alcohol consumption being most common co-morbid conditions and scrotal abscess (53.52%) being the most common presentation. Serum creatinine (p value 0.0008), total leucocyte count at presentation (p value 0.004) had a significant association with duration of recovery. The mean duration of stay was 16.08±3.28 days with a median of 15 days. The Fournier gangrene severity index score calculated was <9 in 59.15% of patients, and >9 in the remaining ≈40% with a mean of 8.309±3.49. A single mortality was recorded during our study. Conclusions: Serum creatinine and total leucocyte count at presentation could play a pivotal role in not only initial emergency management but also as factors for monitoring the progress of treatment.